Analisis Tingkat Kepuasan Pelanggan Atas Kualitas Produk dan Pelayanan CV. Roda Mas Jaya Semarang (Studi Kasus Pada Konsumen CV. Roda Mas Jaya Semarang) - Prayudanto, Aditya Tjahya; Nugraha, Hari Susanta; Wijayanto, Andi (Jurnal Ilmu Administrasi Bisnis, 2013)
The successful key of CV. Roda Mas Jaya Semarang in the field of tire retreading is focus on customer satisfaction in order to survive and dominate the market. In order to improve customerÂ  satisfaction, CV. Roda Mas Jaya Semarang trying to provide the kind of products and services superior facilities that aims to satisfy customers. This research is a descriptive survey approach. Sample was 15 companies were taken using census techniques. Measurement scale with a Likert scale. Data collection by interview using a questionnaire. Data analysis using Cartesian diagram.The results showed that the level of product conformance to customer expectations by 79.31% in the category are satisfied. This means that the performance of the product CV Roda Mas Jaya Semarang meet customers' expectations by 79.31%. Service quality level according to customer expectations by 89.44% in the category are satisfied. This means that the performance of services CV. Roda Mas JayaÂ  Semarang meet customer expectations by 89.44%.Advice can be given for the company is to improve the performance and speed of the product with specifications in the manufacture of products, as well as timeliness in providing services to customers and compliance with the promised service process.